Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Kemampuan Kognitif Siswa Kelas 5 Jabir SD Al-Azhar Syifa Budi Solo - Sisna Marvilia Ayuningrum; Novi Puspita Sari; Riyadi Riyadi; Siti Nureini (Universitas Sebelas Maret, 2025)
Differences in students' cognitive abilities are among the most crucial issues in the field of education. These differences require teachers to provide appropriate facilitation so that all students, regardless of their individual abilities, can achieve the same learning objectives. Differentiated instruction emerges as one of the solutions to address this inequality. This study aims to analyze the impact of implementing differentiated instruction in Mathematics on the cognitive abilities of Grade V Jabir students at SD Al Azhar Syifa Budi Solo. The method used is Classroom Action Research (CAR) with a quantitative approach. Data were collected through observations and written tests. The research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. The research subjects were 25 Grade V students. The results showed that the percentage of students who achieved mastery learning in Cycle 1 was 72%, while in Cycle 2 it increased to 92%. These findings indicate that differentiated instruction is effective in improving students' learning outcomes and is able to accommodate individual learning needs and characteristics.